Muskuloskeletal and reproductive problems among the female workers in batik factories at Kuala Terengganu, 1998 - Kasemani Embong,; KG Rampal, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross sectional study of musculoskeletal and reproductive problems was conducted among the female workers in batik factories at Kuala Terengganu from September to December, 1998. The aim of this study is to determine the prevalence of this problem and the occupational factors that contribute to them. The universal sampling technique was used and all 120 female workers from 9 batik factories in Kuala Terengganu were studied. Chi square and t test were used in determining the association of occupational factors with reproductive and musculoskeletal problem. The study showed that the prevalence of backache (62.5%) was the highest among the musculoskeletal problems followed by wrist (47.5%), neck (25.8%) and knee (18.3%) problems. The prevalence of backache was significantly associated with long duration of standing and bending forward during working (p <0.05). Bending forward also was significantly associated with knee and neck problem. Other occupational factors did not show any significant association with musculoskeletal problem. Common reproductive problems identified were spontaneous abortion with prevalence of 16.7% and premature delivery (1.9%) but there was no significant association between occupational factors and these problems.